Effects of prenatal cocaine exposure on early sexual behavior: Gender difference in externalizing behavior as a mediator. (1st August 2015) - Min, Meeyoung O.; Minnes, Sonia; Lang, Adelaide; Yoon, Susan; Singer, Lynn T.
Highlights: Prenatal cocaine exposure (PCE) is related to sexual intercourse before age 15. Externalizing behavior problems mediated PCE effects in female adolescents. Blood lead during preschool years was also related to early sexual intercourse. Abstract: Background: Prenatal cocaine exposure (PCE) is associated with increased risk for externalizing behavior problems; childhood externalizing behavior problems are linked with subsequent early sexual behavior. The present study examined the effects of PCE on early sexual initiation (sexual intercourse prior to age 15) and whether externalizing behavior in preadolescence mediated the relationship. Methods: Three hundred fifty-four (180 PCE and 174 non-cocaine exposed; 192 girls, 142 boys), primarily African-American, low socioeconomic status, 15-year-old adolescents participated in a prospective longitudinal study. Adolescents' sexual behavior was assessed at 15 years using the Youth Risk Behavior Surveillance System. Externalizing behavior was assessed at 12 years using the Youth Self-Report. Results: Logistic regression models indicated that adolescents with PCE ( n = 69, 38%) were 2.2 times more likely (95% CI = 1.2–4.1, p < .01) to engage in early sexual intercourse than non-exposed peers ( n = 49, 28%) controlling for covariates. This relationship was fully mediated by self-reported externalizing behavior in girls but not in boys, suggesting childhood externalizing behavior as a gender moderated mediator. Blood lead level during preschool years was also related to a greater likelihood of early sexual intercourse (OR = 2.6, 95% CI = 1.4–4.7, p < .002). Greater parental monitoring decreased the likelihood of early sexual intercourse, while violence exposure increased the risk. Conclusions: PCE is related to early sexual intercourse, and externalizing behavior problems mediate PCE effects in female adolescents. Interventions targeting externalizing behavior may reduce early sexual initiation and thereby reduce HIV risk behaviors and early, unplanned pregnancy in girls with PCE.